Cutaneous squamous carcinoma in a patient with diabetic foot: an unusual evolution of a frequent complication. (31st July 2018) - Mantovani, Alessandro; Teobaldi, Ilaria; Stoico, Vincenzo; Perrone, Fabrizia; Zannoni, Marina; Cima, Luca; Bruti, Massimiliano; Mingolla, Lucia; Trombetta, Maddalena; Bonora, Enzo
Summary: After basal cell carcinoma, the cutaneous squamous cell carcinoma (cSCC) is the second most frequent non-melanoma skin cancer worldwide, and, classically, arises from the upper coats of the epidermis of sun-exposed areas or from skin areas constantly exposed to a chronic inflammatory stimulus. The occurrence of cSCC seems to be linked to several factors, including exposure to sunlight (or other ultraviolet radiations), immunosuppression, chronic scarring conditions and some familial cancer syndromes. Although the majority of cSCCs are adequately eradicated by surgical excision, a subgroup of cSCC may be linked with an increased risk of recurrence, metastasis and death. The incidence of type 2 diabetes mellitus is constantly increasing worldwide. Importantly, diabetes mellitus is a strong risk factor for cancers (including cutaneous tumors) and is highly related with poor cancer outcomes. At present, in the literature, squamous cell carcinoma developing in association with diabetic foot ulcers has been already reported in some reports; however, additional data are needed to make the clinicians aware of this rare, although possible, complication. Therefore, we herein report an unusual case of an elderly man with T2DM and a positive oncological history, presenting a cSCC involving the skin overlying the first toe of left foot. The growing cSCC appeared approximately 3 years after the appearance of a diabetic ulcer. Learning points: Diabetic foot ulcers are an important and severe complication of diabetes mellitus and often can result in foot amputation. Chronic and non-healing diabetic foot ulcers are often observed in clinical practice. Clinicians should always take into consideration the malignant degeneration (e.g., cutaneous squamous cell carcinoma) of any chronic non-healing diabetic foot ulcer in elderly T2DM individuals. Timely surgical resection of a chronic, non-healing diabetic foot ulcer might preclude the development of a cutaneous squamous cell carcinoma.